Investigating chorion softening of zebrafish embryos with a microrobotic force sensing system - Kim, DH; Sun, Y; Yun, S; Lee, SH; Kim, B (ELSEVIER SCI LTD, 2005)
The zebrafish is a model organism for addressing questions of vertebrate embryo development. In this paper, the softening phenomenon of the chorion envelope of zebrafish embryos at different developmental stages was mechanically quantitated by using a microrobotic force sensing system. The microrobotic system integrates a piezoelectric cellular force sensor to measure the required forces for penetrating the chorion envelope. Magnitude of penetration forces was found to decrease as an embryo develops. The results mechanically quantitate "chorion softening" in zebrafish embryos due to protease activities subtly modifying the chorion structure, providing an understanding of zebrafish embryo development. 2004 Elsevier Ltd. All rights reserved.
Keywords: INJECTION; FISH